Tunable doping of N and S in carbon nanotubes by retarding pyrolysis-gas diffusion to promote electrocatalytic hydrogen evolution. Issue 67 (5th August 2019) - Wu, Hao; Chen, Zhimin; Xiao, Fei; Wang, Ying; Cao, Erping; Chen, Shuo; Du, Shichao; Wu, Yiqun; Ren, Zhiyu
Abstract : We report a simple retarding pyrolysis-gas diffusion approach that could extensively tune the amount of N and P in carbon nanotubes with a significantly enhanced HER activity. Abstract : The doping amount of heteroatoms in N, S co-doped carbon nanotubes (CNT-NS) was accurately and extensively regulated by retarding pyrolysis-gas diffusion. The effect of the content of N and S on the hydrogen evolution activity of CNT-NS was revealed for the first time both experimentally and theoretically.